Formation and utilisation of acid sulfate soils in Southeast Asia for sustainable rice cultivation - Jusop, Shamshuddin; Panhwar, Qurban Ali; Jamaludin, Alia Farhana; Mohd Ali Raini, Siti Shazana; Othman, Radziah; Ishak, Che Fauziah (Universiti Putra Malaysia Press, 2017)
Large parts of lowland areas in Southeast Asia were submerged in seawater some 4300 years ago due to a rise in sea level. During this period, the coastal plains in the region were pyritised. Agricultural development led to oxidisation of the pyrite (FeS2) which in turn allowed weathered mineral silicates to be present in the sediments. High levels of Al and/or Fe are thus present in the soils/water that affect plants and aquatic life. Rice grown on the so-called acid sulfate soils suffer from low pH and Al 3+ and/or Fe2+ toxicity, with yields below the national average. The critical pH and Al concentration for rice growth is 6 and 15-30 uM respectively. The soil become infertile due to high concentrations of acid sulfate. Application of ground magnesium limestone (GML) or basalt in combination with bio-fertiliser fortified with phosphate-solubilising bacteria (PSB) can help reduce the acid sulfate. The PSB not only excrete organic acids that inactivate Al and Fe via chelation, but also increase soil pH to the level that precipitates Al as inert Al-hydroxides. Additionally, rice roots are able to excrete organic acids under the presence of high concentration of Al and/or Fe, which further reduces the availability of Al and Fe in the water.